Si Magu na "Malansahon" at si Sol, ang White Carabao - Breis, Niles Jordan (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
“Si Magu na Malansahon at si Sol, ang White Carabao” is one of those “small narratives” on/under martial law in the first district of Albay, specifically in Tabaco City. It offers a recollection of what the student-activists then were up to in BUTC (Bicol University – Tabaco City). Also, a quick look at ajax, the moniker for deep penetration agents or DPAs.